The Employment Effects of National Minimum Wage increase on Employment in Nigeria: A Review of Previous Cases - Chilekezi, Obinna (Kashere Journal of Politics and International Relations, 2024)
The responsibility of changing the minimum wage is a constitutional issue vested on the federal government as an item under the Exclusive list. This means that it is only the National Assembly and not the state assemblies that could pass laws on matters pertaining to the minimum wage. Nevertheless, the constitutional provision on minimum wage cannot prevent a state or institutions that wish to pay higher wages not to do so but it however prevent them from paying lesser amounts. On the employment effect of the minimum wage, it is important to note that economic theory suggested that an increase in product’s price will lead to a decline for the product which could be applicable to supply of labour. The research methodology adopted for this study is the ddescriptive qualitative research design. This was used to investigate the employment effects of an increase on the National Minimum Wage to the labour market. The reviewed literatures on employment effect generally showed that an increase minimum wage could lead to reduction of demand for employment. This position is not different from that of the Nigerian experience, starting from 1981 when the first minimum wage law was enacted in the country. More so, the findings also showed that as a result of this most states and private sector employers had avoided the implementation of the minimum wage in order not reduce the level of their workforce.